Multi-output buck-boost converter with enhanced dynamic response to load and input voltage changes - Boora, A.; zare, F.; Ghosh, Arindam (The Institution of Engineering and Technology, 2011)
This study presents a new multi-output DC/DC converter topology that has step-up and step-down conversion capabilities. In this topology, several output voltages can be generated and can be used in different applications such as multilevel converters with diode-clamped topology or power supplies with several voltage levels. Steady-state and dynamic equations of the proposed multi-output converter have been developed; these can be used for steady state and transient analysis. Two control techniques have been proposed for this topology, based on constant and dynamic hysteresis band heightcontrol, to address different applications. Simulations have been performed for different operating modes and load conditions to verify the proposed topology and its control technique. Additionally, a laboratory prototype is designed and implemented to verify the simulation results.